1999
DOI: 10.1029/1999jd900825
|View full text |Cite
|
Sign up to set email alerts
|

Methyl bromide emissions from agricultural field fumigations in California

Abstract: Abstract. Methyl bromide is the most abundant brominated hydrocarbon gas in the atmosphere and is significant as a source of stratospheric bromine radicals that destroy ozone. However, estimated sources and sinks of methyl bromide exhibit a deficit in sources of--•70 Gg/yr (one Gg -109 g), and the proportion of natural and anthropogenic sources is not known well. Known sources include agricultural fumigation (preplant and postplant), structural fumigation, biomass burning, gasoline additives, and oceans. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
(7 reference statements)
0
6
0
Order By: Relevance
“…Atmosphere and coupled ocean‐atmosphere box‐model calculations [ Butler , 1994] were performed for CH 3 Br with time‐varying industrial emissions that were derived from production data reported to UNEP [1998], and additional constant emissions required to match the measured mixing ratios in 1995–1997. The calculation C 1 included a global lifetime of 0.7 yr, total CH 3 Br emissions of 205 Gg yr −1 in 1992, and an emission fraction ( f ) of 0.5 [ Williams et al , 1999] for industrially produced CH 3 Br applied to soils. Results from a range of calculations (represented by C 2 ) were derived with an [anthropogenic]/[global] emission fraction of 40–45% in 1996 (obtained with lifetimes of 0.8 < τ < 1.5 yr and corresponding releases from soils of 1.0 > f > 0.7).…”
Section: Methodsmentioning
confidence: 99%
“…Atmosphere and coupled ocean‐atmosphere box‐model calculations [ Butler , 1994] were performed for CH 3 Br with time‐varying industrial emissions that were derived from production data reported to UNEP [1998], and additional constant emissions required to match the measured mixing ratios in 1995–1997. The calculation C 1 included a global lifetime of 0.7 yr, total CH 3 Br emissions of 205 Gg yr −1 in 1992, and an emission fraction ( f ) of 0.5 [ Williams et al , 1999] for industrially produced CH 3 Br applied to soils. Results from a range of calculations (represented by C 2 ) were derived with an [anthropogenic]/[global] emission fraction of 40–45% in 1996 (obtained with lifetimes of 0.8 < τ < 1.5 yr and corresponding releases from soils of 1.0 > f > 0.7).…”
Section: Methodsmentioning
confidence: 99%
“…This creates a series of panels down the field and a continuous plastic cover over the field. MeBr application rates range from 200 kg/ha to 400 kg/ha and large fractions (24% to 74%) of the applied chemical are lost to the atmosphere (Yagi et al, 1993(Yagi et al, , 1995Majewski et al, 1995;Yates et al, 1996b,c;Williams et al, 1999). Yates et al (1996a,b,c) conducted a field experiment to investigate the environmental fate and transport of MeBr after soil fumigation.…”
Section: Introductionmentioning
confidence: 99%
“…Higher plants have been shown to produce atmospheric CH 3 Cl and CH 3 Br through a methyltransferase reaction [ Saini et al , 1995] and CH 3 Br through soil Br‐ conversion in live plants from the Brassicaceae family [ Gan et al , 1998]. These natural sources of CH 3 Br are significant contributors to a global budget once thought to be dominated by anthropogenic sources such as biomass burning [ Andreae et al , 1996], fumigation [ Yagi et al , 1993, 1995; Butler and Rodriguez , 1996; Yates et al , 1997; Williams et al , 1999b], and gasoline combustion [ Thomas et al , 1997; Chen et al , 1999; Baker et al , 1998].…”
Section: Introductionmentioning
confidence: 99%